Estimation of the traffic accidents costs in Serbia by using dominant costs model - Antić, Boris; Vujanić, Milan; Lipovac, Krsto; Pešić, Dalibor (Transport, 2011)
This paper presents estimation of the traffic accident costs in Serbia, based on original dominant costs model. Dominant costs model uses human capital approach and this model is developed for simple and quick calculation of the traffic accidents costs, because other simple methods as 1 million rules, are not suitable for estimation of the traffic accident costs in the countries with a low GDP per capita. Knowing the costs of traffic accidents is of crucial importance for establishing traffic safety to the level defined by the size of costs made as a consequence of unsafely. So, politicians, decision makers and stakeholders in the field of traffic safety often need quick estimation of the traffic accident costs and economic effects of the particular measures which are applied for decreasing the number and severity of traffic accidents. The estimation of the level of the traffic accidents costs in Serbia, based on the official data (from the Ministry of Interior of the Republic of Serbia) about traffic accidents in Serbia for 2008 is shown in this paper and the comparison between predicted and calculated value of the traffic accident costs for 2009 is also presented. First Published Online: 09 Jan 2012